Cabinet Structure during the State Financial Crisis: A Comparison of Budget Efficiency Policies between Indonesia and Argentina - Vianti Nur Mauliddya Ike Safitri; Berrahlia, Badreddine; Alammari, Khalid Saleh Y (Journal of Indonesian Constitutional Law, 2025)
This study examines the financial crises in Indonesia and Argentina, focusing on the cabinet structure policies of these two countries. It aims to examine the policy models of the Indonesian and Argentine governments for restructuring their cabinets in response to the crisis while also implementing budgetary efficiency measures. This study contributes to the development of an adaptive and efficient model for cabinet restructuring in response to financial crises, and can serve as a reference for the formulation of fiscal and institutional policies. The study employs a doctrinal legal research method with a statute and comparative approach. The findings indicate that Indonesia’s operational expenditures are high; however, political considerations have resulted in inefficiencies, such as the expansion of ministries from 34 to 48. Indonesia’s fiscal efficiency remains inconsistent due to political limitations. In contrast, Argentina has enacted comprehensive and more decisive reforms, reducing the number of ministries from 18 to 8 and implementing extensive cuts across the government. Therefore, the results suggest that Indonesia’s policies are constrained by political and legal constraints, whereas Argentina’s approach relies on strong executive decrees. This study recommends that Indonesia consider merging related ministries and streamlining bureaucratic structures in accordance with national circumstances. Additionally, it proposes strengthening executive governance through legal reforms, such as establishing a formal presidential office and restricting the scope of non-essential institutions, to improve budget efficiency.